Comparison of pathophysiology in subclinical hyperthyroidism with different etiologies - Hanna Deguchi-Horiuchi; Mitsuru Ito; Sawako Takahashi; Kazuyoshi Kousaka; Mako Hisakado; Shuji Fukata; Takumi Kudo; Eijun Nishihara; Mitsushige Nishikawa; Akira Miyauchi; Takashi Akamizu (Endocrine Journal)
Subclinical hyperthyroidism (SHyper) is defined as normal levels of free thyroxine (fT4) and free triiodothyronine (fT3) with suppressed levels of TSH. Previous studies have reported the individual pathophysiology of endogenous SHyper patients and athyreotic patients receiving TSH suppression therapy with levothyroxine; however, apparently no studies have compared the two conditions. Five-hundred-forty untreated endogenous SHyper patients and 1,024 patients receiving TSH suppression therapy who underwent total thyroidectomy for papillary thyroid carcinoma were sampled. Thyroid hormone profiles and peripheral indices related to thyrotoxicosis were investigated in endogenous SHyper patients, athyreotic patients receiving TSH suppression therapy, and healthy participants. Endogenous SHyper patients showed significantly higher thyroid hormone levels (fT4 [p < 0.001] and fT3 [p < 0.001]), and peripheral indices showed a significant tendency towards thyrotoxicosis (strong TSH suppression: alkaline phosphatase [ALP, p < 0.001], creatinine [Cre, p < 0.001], pulse rate [p < 0.05]; and mild TSH suppression: Cre [p < 0.05]) than healthy participants. In contrast, athyreotic patients receiving TSH suppression therapy showed a significant tendency towards thyrotoxicosis than healthy participants only when TSH was strongly suppressed (fT3 [p < 0.001] and Cre [p < 0.001]). Endogenous SHyper patients showed significantly higher fT3 levels (p < 0.001) than athyreotic patients receiving TSH suppression therapy; however, there was a significant tendency towards thyrotoxicosis only when TSH was strongly suppressed (ALP [p < 0.05] and pulse rate [p < 0.05]). The effects of endogenous SHyper and TSH suppression therapy on target organ function are different. Although the serum thyroid hormone profile is similar to that of the thyrotoxic state, athyreotic patients receiving TSH suppression therapy with mildly suppressed serum TSH levels are not thyrotoxic.